Carbon quantum dots/nickel oxide (CQDs/NiO) nanorods with high capacitance for supercapacitors. Issue 7 (12th January 2016) - Xu, J.; Xue, Y.; Cao, J.; Wang, G.; Li, Y.; Wang, W.; Chen, Z.
Abstract : Novel CQDs/NiO nanorods have been prepared via a facile complexation method followed by a thermal treatment process and used as electroactive materials for supercapacitors, which deliver a high specific capacitance of 1858 F g −1 at 1 A g −1 . Abstract : Novel one-dimensional composites of carbon quantum dots (CQDs) coated NiO nanorods have been prepared via a facile complexation method followed by a thermal treatment process with no addition of organic solvent or surfactant. The carbon quantum dots/NiO (CQDs/NiO) nanorods are very uniform in size with an average length of about 800 nm and diameter of 30 nm. The CQDs/NiO hybrid nanorods deliver a high specific capacitance (1858 F g −1 at 1 A g −1 ), exceptional rate capability (84.6%, 75.7%, 65.3%, 56.1% and 51.5% capacity retention rate at 2, 3, 5, 7 and 10 A g −1, respectively) and excellent cycling stability (93% of the initial capacity retention over 1000 cycles at 2 A g −1 ) due to the coupled effect of faradaic pseudocapacitance from the NiO nanorods and the excellent electrical conductivity of the CQDs. These outstanding electrochemical performances demonstrate that the CQDs/NiO nanorods are efficient electrode materials and have a greatly promising application in the development of high-performance electrochemical energy storage devices.